Android Educational Game “MATHOLIC” Based on Van Hiele’s Geometric Thinking Level on Plane Figures - Windu Wiyana; Yuniawatika Yuniawatika; Tri Murti; Mohamad Waluyo (Profesi Pendidikan Dasar, 2022)
The objective of this study was to produce an educational game based on Van Hiele’s geometric thinking level called “MATHOLIC” on plane figures material in fourth-grade elementary school. This research was Research and Development (RD), which used the ADDIE model. The subjects of this study were fourth-grade students of Tlumpu Blitar State Elementary School. The data collection instruments were interview guidelines and questionnaires. The data was obtained in the form of qualitative data and quantitative data. The results of this study showed that: (1) the material experts gave the level validity of MATHOLIC 95,8%, while media experts gave the validity level of MATHOLIC 94,4%, and the classroom teacher gave the level validity of 98%, which meant that MATHOLIC was very valid; (2 )student responses in small group trials obtained a percentage of the practicality was 95% and in the field trial was 97,7% which meant that MATHOLIC was very practice; (3) the average score was 87,7 in the small group trial and 96,4 in the field trial which meant that the average was already above the Minimum Completeness Criteria score. MATHOLIC was declared valid and practical to be suitably used in learning mathematics. This study showed the validity and practicality of learning media in educational games that use van Hiele's theory. The findings of this study will be a solution for teachers who have difficulty teaching the material of plane figures  to make it more effective and easily understood.